About 3-methoxypropyltin(IV) compounds - Smička, Aleš; Handlíř, Karel (Univerzita Pardubice, 2002)
A set of novel 3-methoxypropyltin (IV) compounds of the general formula (CH3 OCH2 CH2 CH2) SnCl 4-x (x=1-4) was synthesized and characterized. Shape of the coordination polyhedra about central tin atom and character Sn-O interaction are discussed on the basis of multinuclear NMR spectra, IR spectra and X-ray structure determination. Enhanced water solubility of these compounds was observed.
Keywords: 3-methoxypropyltin(IV); sloučeniny cínu; syntézy; vlastnosti látek; spektroskopické metody; struktura látek